PELAKSANAAN PEMBERIAN KOMPENSASI ATAS KETERLAMBATAN PENERBANGAN KEPADA PENUMPANG MASKAPAI SUPER AIR JET - NIM. A1011221263, LUDGARDIS LAURA REGIS SARI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Flight delays constitute a significant issue in the administration of air transportation in Indonesia and have a direct impact on the fulfillment of passengers’ rights. The high frequency of delays experienced by Super Air Jet, as reflected in its relatively low On Time Performance (OTP), has resulted in both material and immaterial losses for passengers. In the air carriage contract, airlines are obligated to provide compensation, while passengers are entitled to receive such compensation in accordance with the category of delay. Therefore, this study aims to examine the legal framework governing flight delays and the implementation of compensation provided by Super Air Jet. This research employs an empirical legal research method with a juridical-sociological approach. Primary data were obtained through interviews with airline representatives, Airport Authority officials, and passengers who experienced flight delays during the period of June to November 2025. Secondary data were collected through a literature review of relevant laws, regulations, and academic publications. Data analysis was conducted qualitatively through data reduction, data presentation, and conclusion drawing in order to describe the implementation of compensation for delayed passengers. The findings indicate that the legal regulation of flight delays is based on the legal relationship between the carrier and passengers under the air carriage contract, as stipulated in Law Number 1 of 2009 on Aviation and Minister of Transportation Regulation Number 89 of 2015. These regulations provide legal protection for passengers’ rights to information, basic services, and compensation according to the category of delay. However, the existing legal framework cannot yet be considered an effective compensation mechanism, as the compensation provided is standardized and does not fully reflect the actual losses suffered by passengers. In the case of Super Air Jet, the implementation of compensation varies significantly and largely depends on the airline’s operational readiness and discipline. Furthermore, supervision by the Airport Authority remains limited and predominantly administrative in nature, causing the fulfillment of passengers’ rights to rely heavily on airline compliance, particularly in cases of sudden delays. Internal factors such as operational constraints and human resource limitations, as well as external factors including weather conditions and inadequate airport facilities, also contribute to inconsistencies in the implementation of compensation. These findings demonstrate that although a regulatory framework is in place, the practical implementation of passenger compensation has not been evenly or optimally enforced. Keywords: Flight Delays, Super Air Jet, Compensation Abstrak Keterlambatan penerbangan merupakan permasalahan signifikan dalam penyelenggaraan angkutan udara di Indonesia yang berdampak langsung pada pemenuhan hak penumpang. Tingginya frekuensi keterlambatan penerbangan Maskapai Super Air Jet, yang tercermin dari capaian On Time Performance (OTP) yang relatif rendah, menimbulkan kerugian baik materiil maupun immateriil bagi penumpang. Dalam perjanjian pengangkutan udara, maskapai memiliki kewajiban memberikan kompensasi, sementara penumpang berhak menerima ganti rugi sesuai kategori keterlambatan. Oleh karena itu, penelitian ini bertujuan untuk mengkaji pengaturan hukum keterlambatan penerbangan serta pelaksanaan pemberian kompensasi oleh Maskapai Super Air Jet. Penelitian ini menggunakan metode penelitian hukum empiris dengan pendekatan yuridis-sosiologis. Data primer diperoleh melalui wawancara dengan pihak maskapai, Otoritas Bandar Udara, serta penumpang yang mengalami keterlambatan penerbangan pada periode Juni hingga November 2025. Data sekunder dihimpun melalui studi kepustakaan terhadap peraturan perundang-undangan dan literatur ilmiah yang relevan. Analisis data dilakukan secara kualitatif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan untuk menggambarkan pelaksanaan pemberian kompensasi kepada penumpang. Hasil penelitian menunjukkan bahwa pengaturan hukum mengenai keterlambatan penerbangan berlandaskan hubungan hukum antara pengangkut dan penumpang dalam perjanjian pengangkutan udara, sebagaimana diatur dalam Undang-Undang Nomor 1 Tahun 2009 tentang Penerbangan dan Peraturan Menteri Perhubungan Nomor 89 Tahun 2015. Regulasi tersebut memberikan perlindungan terhadap hak penumpang berupa informasi, pelayanan dasar, dan kompensasi sesuai kategori keterlambatan. Namun, pengaturan ini belum sepenuhnya efektif karena kompensasi yang diberikan bersifat standar dan belum mencerminkan kerugian riil yang dialami penumpang. Pada praktiknya, pelaksanaan kompensasi oleh Super Air Jet sangat bergantung pada kesiapan operasional dan kedisiplinan maskapai. Selain itu, pengawasan oleh Otoritas Bandar Udara masih terbatas dan cenderung administratif, sehingga pemenuhan hak penumpang lebih bergantung pada kepatuhan maskapai. Faktor internal seperti kendala operasional dan sumber daya manusia, serta faktor eksternal berupa kondisi cuaca dan keterbatasan fasilitas bandar udara, turut memengaruhi ketidaksesuaian pelaksanaan kompensasi. Temuan ini menegaskan bahwa meskipun kerangka regulasi telah tersedia, implementasi kompensasi belum berjalan optimal dan merata. Kata Kunci: Keterlambatan Penerbangan, Super Air Jet, Kompensasi